Book Review: Murphy, J.T. and Carmody, P. 2015: Africa's Information Revolution: Technical Regimes and Production Networks in South Africa and Tanzania. (October 2017) - Wanjiru, Roseline
Murphy, J.T. and Carmody, P. 2015: Africa's Information Revolution: Technical Regimes and Production Networks in South Africa and Tanzania . Chichester, UK: Wiley. 249 pp. £60.00 (Hardcover), £24.99 (Paperback). ISBN: 9781118751329 (Hardcover), ISBN: 9781118751336 (Paperback).